Character Development of Pancasila Student Profiles Through Creative Dance Learning for Mild Mental Mental Disability Students - Febiana Febiana (Pinisi Journal of Social Science, 2022)
The purpose of this study is to find out how to develop the character profile of Pancasila students through learning dance creations. This study uses a qualitative approach. Data collection techniques used are observation, interviews, and documentation studies. Data processing techniques by trialing. Time and place of research during the first semester starting from January 10, 2022 to June 10, 2022 at SLB-C Sukapura, Bandung City. The research subjects in this study were 6 students with mild mental retardation in class VII SLB-C Sukapura. The results of the research are that the development of the Pancasila student profile character through creative dance learning for mild mentally retarded students can run effectively when the teacher can carry out learning organization well. The teacher plans learning based on the results of the assessment, choosing a positive song accompaniment, compiling creative dance material gradually according to the characteristics of students with mild mental retardation, inculcating the Pancasila student profile character which is carried out directly and indirectly through the creative dance learning process so that it becomes a habit, strengthening positive in learning, as well as evaluations carried out during the process and at the end of learning. With consistent dance training and character planting in dance learning, the 6 dimensions of the Pancasila student profile have a more positive impact on the character of mild mentally retarded students so as to help mild mentally retarded students to behave positively in their daily lives.